Effect of Morinda citrifolia L., citric acid, and Lactobacillus acidophilus on broiler growth performance, carcass traits, and litter quality - Mahfudz, L. D.; Ma'rifah, B.; Suprijatna, E.; Sunarti, D.; Kismiati, S.; Sarjana, T. A.; Muryani, R.; Shihah, H. D.; Wahyuni, N. M. (Diponegoro University, 2025)
This study evaluated the effect of a feed additive combination, Morinda citrifolia leaf extract, citric acid, and Lactobacillus acidophilus (MCL) on broiler chicken performance, carcass traits, and litter quality. MCL contains bioactive compounds such as flavonoids, saponins, citric acid, and probiotic. A total of 200 broiler chickens (8 days old with average body weight 213.88 ± 8.9 g) were randomly assigned to four treatments with five replications of bird each: T0 (control), T1 (1% MCL), T2 (2% MCL), and T3 (3% MCL). Results showed that T2 significantly improved (P<0.05) body weight gain (BWG) and income over feed cost (IOFC). Water consumption and carcass weight were also higher (P<0.05) in T2. Final body weight was significantly higher (P<0.05) in all MCL treatments compared to T0. Feed conversion ratio improved (P<0.05) in T2 and T3. MCL supplementation enhanced carcass traits and litter quality. Cooking loss was lower (P<0.05) in T2, while drip loss and litter pH were reduced (P<0.05) in all MCL treatments. White striping was higher (P<0.05) in T1, and litter temperature was lower (P<0.05) in T2 and T3. These finding suggest that MCL is a promising natural alternative to synthetic growth promotors, improving productivity and probitability in broiler production.